2023
DOI: 10.3389/fsurg.2022.960721
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and sexual activity in young total hip arthroplasty Chinese patients: A retrospective cohort study

Abstract: IntroductionAs an essential component of quality of life, there is limited evidence of sexual function (SF), especially for young patients, before and after total hip arthroplasty (THA). This study aims to enhance the understanding of SF status and assess patient perspectives before and after THA.MethodsA total of 109 patients who received THA were enrolled into our retrospective cohort study. To assess the SF status before and after THA, patients were required to fill out a standardized SF questionnaire [fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 32 A previous study analyzing sexual function in young adults pre-THA demonstrated difficulty in 64% of patients, almost equal to our findings. 33 Sexual activity has a large bearing on QoL, and correlates with mental wellbeing and physical health; however, further commentary on this goes beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 32 A previous study analyzing sexual function in young adults pre-THA demonstrated difficulty in 64% of patients, almost equal to our findings. 33 Sexual activity has a large bearing on QoL, and correlates with mental wellbeing and physical health; however, further commentary on this goes beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 93%
“…32 A previous study analyzing sexual function in young adults pre-THA demonstrated difficulty in 64% of patients, almost equal to our findings. 33 Sexual activity has a large bearing on QoL, and correlates with mental wellbeing and physical health; however, further commentary on this goes beyond the scope of this paper. Despite low rates of revision and complications, the relatively high proportion of patients not returning to pre-morbid function indicates the complexity of operating in this cohort.…”
Section: Discussionmentioning
confidence: 93%